Business robot farm management in the Robotic Process Automation (RPA) - Marciniak, Piotr (Zielona Góra: Faculty of Economics and Management Press)
The growing demand for innovative IT solutions allowed the existing industries to develop and enabled the emergence of new ones, which filled the existing technological gaps. Among them, we could observe a dynamic growth of the robotic process automation sector. Business robots are designed to automate the organization`s business processes by imitating real users performing their daily duties, which are based on structured, repetitive procedures, increasing the operational efficiency of the organization while reducing the impact of the human factor.
Keywords: robotic process automation; RPA farm; automation management; software robots